2011
DOI: 10.3327/jnst.48.483
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sensors for On-Line Monitoring of Nonmetallic Impurities in Liquid Sodium

Abstract: Sensors for on-line monitoring of hydrogen and carbon in sodium and hydrogen in argon cover gas circuits over sodium have been developed. The performance of these sensors in fast breeder test reactor (FBTR) and large sodium facilities is evaluated. A sensor for monitoring oxygen in sodium is under development. The in-sodium electrochemical hydrogen sensors are found to detect about 10 ppb increase in hydrogen concentration over a background of 50 ppb. The cover gas hydrogen monitoring sensor system is found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Even if yttrium-doped thoria is generally considered to be much less sensitive to sodium corrosion compared to zirconia [16], also frequently used in oxygen sensors [17], only very few studies are reported in the literature regarding its chemical durability. Indeed, different potential failures were evidenced, but appear to be mainly linked with mechanical effects [16,[18][19][20][21]. Fractures often occurred very rapidly after contact with liquid sodium between 360 and 400°C, but more likely due to thermal shock rather than to sodium corrosion [16,22].…”
Section: Introductionmentioning
confidence: 99%
“…Even if yttrium-doped thoria is generally considered to be much less sensitive to sodium corrosion compared to zirconia [16], also frequently used in oxygen sensors [17], only very few studies are reported in the literature regarding its chemical durability. Indeed, different potential failures were evidenced, but appear to be mainly linked with mechanical effects [16,[18][19][20][21]. Fractures often occurred very rapidly after contact with liquid sodium between 360 and 400°C, but more likely due to thermal shock rather than to sodium corrosion [16,22].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the presence of impurities in the ceramic, and particularly within grain boundaries, was systematically associated to an increase of the corrosion rate in liquid sodium [19], and sometimes to the formation of secondary phases such as Na2ThSiO5 or Na2SiO5 at the surface of the electrolyte [12]. Nowadays, no more commercial oxygen sensors for sodium are available, and the sensor development is limited to few laboratories in India [8,20], USA [9] and France.…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of alkaline earth hydrides along with alkaline earth halides is employed as the electrolyte for this purpose. [2][3][4] CaCl 2 -CaH 2 3 and CaBr 2 -CaH 2 5 pseudo-binary systems were identified as thermodynamically stable systems for the development of such an electrolyte. In these systems, the compounds CaHCl and CaHBr are the hydride ion conductors.…”
Section: Introductionmentioning
confidence: 99%